ANALISIS RETURN SAHAM BERDASARKAN STRATEGI DOGS OF THE DOW PADA IHSG DI INDONESIA - Gunawan, Reinandus Aditya (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
Every investor is looking to earn positive return on stock investment and they hope to beat the market return. One of the most widely used methods of stock selection is the Dogs of the dow method. This method uses the selection of 10 stocks that have the highest dividend yield as a portfolio formation method. After the formation, the stock portfolio return compared with the return of IHSG as measured by price difference for a year. The result of this study is the fact that of the ten stocks selected each year only the highest dividend shares that can beat the market even though the results are not significant.